Swimming, grazing and social behaviour of rohu Labeo rohita (Hamilton) and common carp Cyprinus carpio (L.) in tanks under fed and non-fed conditions - Rahman, Mohammad Mustafizur; Verdegem, Marc C.J.; Nagelkerke, Leopold A.J.; Wahab, Md Abdul; Verreth, Johan A.J. (Elsevier B.V., 2008)
Fish behaviour was monitored in 1-m2 tanks each stocked with three 67-g rohu (Labeo rohita). In addition, 80-g common carp (Cyprinus carpio) were stocked at 0, 1 or 2 fish per tank. All tanks were fertilized prior to stocking to stimulate natural food production. In addition, half of the tanks were fed a supplemental diet. Results confirmthe general view that rohumainly lives and feeds in thewater column, while common carp is a bottomfeeder. In the presence of commoncarp, rohu increased the time spend grazing on tank wall and bottom, and decreasing grazing time in the water column. Supplemental feeding had a similar, be it less pronounced effect. When both present, rohu and common carp spend 47–52% of their time together. Rohu spends more time close to the bottomin the presence of common carp thanwhen no common carp is present, presumably to profit from increased zooplankton production, triggered by the resuspension of nutrients by burrowing common carp. This was reflected in a higher growth rate of rohu in the presence of carp. These effects were stronger with one commoncarp per tank thanwith two commoncarp. In this study, the results frombehavioural observations in tanks nicely complemented results from a pond study analyzing growth, production and food availability. Behavioural observations in tank yielded useful additional information helpful to clarify species interactions and feeding ecology in polyculture ponds.